2020
DOI: 10.1136/neurintsurg-2019-015418
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and diagnosis of cerebral aneurysms in the post-International Subarachnoid Aneurysm Trial (ISAT) era: trends and outcomes

Abstract: BackgroundFollowing publication of the International Subarachnoid Aneurysm Trial (ISAT), treatment paradigms for cerebral aneurysms (CAs) shifted from open surgical clipping to endovascular embolization as primary therapy in a majority of cases. However, comprehensive analyses evaluating more recent CA diagnosis patterns, patient populations and outcomes as a function of treatment modality remain rare.MethodsThe National Inpatient Sample from 2004 to 2014 was reviewed. Aneurysmal subarachnoid hemorrhages (aSAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…Keyword analysis results showed that the words vascular disorders, flow diverter, delayed cerebral ischemia, pipeline embolization device, stent-assisted coiling, morphology, computational fluid dynamics, microsurgical clipping, and endovascular coiling were among the trend keywords, indicating the research popularity of the endovascular treatments in recent 2020) reported that endovascular treatments are more popular than clipping surgeries in the treatment of intracranial aneurysms. 27 Only one study was found to have had a bibliometric analysis of the studies on intracranial aneurysms. The study analyzed the studies published between 1991 and 2002 regarding China's growing contribution to global intracranial aneurysms research.…”
Section: Discussionmentioning
confidence: 99%
“…Keyword analysis results showed that the words vascular disorders, flow diverter, delayed cerebral ischemia, pipeline embolization device, stent-assisted coiling, morphology, computational fluid dynamics, microsurgical clipping, and endovascular coiling were among the trend keywords, indicating the research popularity of the endovascular treatments in recent 2020) reported that endovascular treatments are more popular than clipping surgeries in the treatment of intracranial aneurysms. 27 Only one study was found to have had a bibliometric analysis of the studies on intracranial aneurysms. The study analyzed the studies published between 1991 and 2002 regarding China's growing contribution to global intracranial aneurysms research.…”
Section: Discussionmentioning
confidence: 99%
“…There are two approaches for treating these patients. The first one is clipping the aneurysm by microdissection using microscope under open surgery, and the other one is endovascular coiling which has improved within the last 10 years [25]. For classification of these patients, brain CT and Fisher scale, Hunt and Hess scale, modified Rankin score and World Federation of Neurological Surgeons (WFNS) scales are used [26].…”
Section: Discussionmentioning
confidence: 99%
“…Irregular domes have unstable walls and are prone to rupture [12]. In the literature, surgery has been shown to offer higher stability along with a lower need for retreatment in comparison to endovascular methods [13]. Aneurysms treated by endovascular treatment have more frequent rebleeding and require more frequent retreatments than surgery [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been documented that the mortality rate in SAH treated patients has decreased over time [13]. Despite the advancements of the modern neurosurgical era such as microscopes and other adjuncts (e.g., indocyanine-green videoangiography), further advances in the management of an ACoAA can still be made in endovascular methods and microsurgical techniques as well as in intensive care treatment [15].…”
Section: Discussionmentioning
confidence: 99%